Makna dan Fungsi Syair Pengiring Kesenian Sintren di Desa Luwijawa Kecamatan Jatinegara - Nurkhayatun, Umi; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
This research was motivated by the lack of knowledge of researchers about the meaning reflected in the accompaniment of the traditional art of Sintren in Luwijawa Village, Jatinegara District, Tegal Regency. The text of the tembang poem has many reflections in the form of meaning and basic functions, both implied and explicit, that exist so that it creates a certain interpretation of the tembang rhyme. The formulation of the problem in this study is how the meaning and function of the accompaniment of the traditional art of Sintren poetry in Luwijawa Village, Jatinegara District, Tegal Regency are. The purpose of this research is to explain how the meaning and function of the accompaniment of the traditional art of Sintren in Luwijawa Village, Jatinegara District, Tegal Regency. The methodology used in this study used descriptive qualitative research methods. The source of this research data is in the form of an oral text that has been transliterated into a written text of poetry that accompanies the traditional art of Sintren in Luwijawa Village, Jatinegara District, Tegal Regency with research data in the form of words, phrases, clauses, sentences and discourses in it. Data collection techniques used were observation, interviews, recording, recording and translating data derived from the traditional art accompaniment of Sintren poetry. Then the data that has been collected is analyzed using data reduction techniques, data classification, and data presentation. Based on data analysis, the results of the study can be stated that in the text of the song lyrics accompanying the traditional art of Sintren found meaning in the form of meaning and function according to the song lyrics in each part.